Bison Jump Location is Primarily Predicted by Minimizing Visibility at the Wold Site, Johnson County, Wyoming. Issue 4 (October 2016) - Grund, Brigid S.; Pelton, Spencer R.; Surovell, Todd A.; Matthews, Neffra A.; Noble, Tommy A.
Abstract : The Wold Bison Jump (48JO966) is a communal bison (Bison bison) hunting site in Johnson County, Wyoming. It likely represents a single kill event precipitated by Great Plains foragers between A.D. 1433 and 1643. Operating the jump required that prehistoric hunters drive stampeding bison up a steep slope in order to position them within a V-shaped drive line configured to funnel them toward a cliff. Using iterative models of least cost paths, topographic cross-sections, and visibility analysis, we test which landscape-embedded variables are optimized at the jump site as compared to other potential localities across the study area. We find that this site's placement is primarily explained by minimizing the distance at which the cliff face is visible and secondarily by minimizing the cost of slope and curvature routes ascending into the drive lines. Our procedure could hypothetically be used to predict optimal jump locations on similar landscapes.